CHARACTERIZATION OF PRODUCERS AND DYNAMIC INNOVATION ADOPTION OF THE MUNICIPALITY OF VILLA VICTORIA, STATE OF MEXICO - Anastacio Espejel-García; Ariadna Isabel Barrera-Rodríguez; Alfredo Rodríguez-Moreno; María de Lourdes Santiago-Vargas (Ra Ximhai, 2015)
In the value chain the first link is made up of different layers, they have different production systems and heterogeneity in adopting innovations. There validated innovations for sheep production system that improve the efficiency of breeding and lamb production, however their adoption depends on endogenous and exogenous factors, which determine the progress or stagnation of the productive and reproductive parameters its production unit livestock (UPP). By applying a Baseline Survey (ELB) and Survey Final Line (ELF), technical-productive and innovation adoption data were collected, in which he characterized the producer, the structure of production units, and is analyzed and the dynamics of innovation. The rate of adoption of innovations (INAI) and the Innovation Gap Adoption indicate that after training and technical assistance provided by a service agency extension, sheep producers in the region of Villa Victoria managed to adopt innovations that influenced the parameters productive and reproductive UPP. The production parameters had significant to increase the percentage of weaning 47-74% advance, decreased the percentage of weaning mortality and adult mortality 26% and 3.9% respectively. Fertility increased from 69.5 to 79% was recorded, prolificacy increased by 9.8% and calving interval decreased approximately one month. Based on the INAI three layers of sheep producers they were determined based on their years of experience in the business, and by analysis of variance with SAS program a statistically significant difference (p <0.05) between the ELB and obtained ELF thereby conclude that the intervention (training and technical assistance) managed to generate a dynamic of adoption of innovations allowing more producers enter the productive and reproductive indicators of the UPP.